Clinical Outcomes of Remdesivir in Moderate and Severe Cases of COVID-19: A Retrospective Cohort Study - Ruth Priya Senthiappan; Archana A Dambal; Mohan Kashinkunti; Kiran R Aithal; Rajendra Kumar Parakh; Bhargav Vuppumalla (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Remdesivir is a nucleotide analogue prodrug that perturbs viral replication. Remdesivir has been used in various trials previously for the treatment of Coronavirus Disease 2019 (COVID-19). Some clinical trials found that remdesivir had a mortality benefit, while other studies did not. It was also seen that remdesivir shortened the duration of hospital stay among COVID-19 patients in some trials while in other trials remdesivir did not have any influence on the duration of hospital stay. Aim: To study the clinical outcomes of Remdesivir in moderate and severe cases of COVID-19. Materials and Methods: The present retrospective, cohort study was conducted in the Department of General Medicine, SDM Medical College and Hospital, Dharwad, Karnataka, India, from September 2021 to May 2022, in which 400 case records of patients admitted with moderate to severe COVID-19 were studied. Among these 314 patients received remdesivir and 86 patients did not receive remdesivir. Categorical variables, nominal variables were represented as proportions and frequencies and continuous variables were represented as mean±SD. Statistical analysis was done using Chi-square test. Results: A total of 400 COVID-19 patients were included in the study, among which 314 received remdesivir and 86 did not receive remedisivir. Those who received remdesivir had a mortality rate of 13.69% as compared to 11.63% among those who did not receive remdesivir (p-value=0.6170). In the remdesivir group, 36.62% had a hospital stay of >11 days, while it was 30.23% among the non remedisivir group (p-value=0.3060). Conclusion: In this study, remdesivir did not reduce mortality nor did it reduce the duration of hospital stay among moderate to severe COVID-19 patients.